Synthesis of Lower Olefins from C3–C4 Alkanes on ZSM-5 Zeolites Modified with Alkali Metals; Russian Journal of Physical Chemistry A; Vol. 74, Suppl. 3 : Modern Tendencies in Kinetics and Catalysis - Trofimova A. S. (2000, 2000)
В фонде НТБ ТПУ отсутствует